2007
DOI: 10.1042/cs20070107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the role of glucocorticoids in the early life programming of adult disease

Abstract: Compelling epidemiological evidence suggests that exposure to an adverse intrauterine environment, manifested by low-birth weight, is associated with cardiometabolic and behavioural disorders in adulthood. These observations have led to the concept of 'fetal programming'. The molecular mechanisms that underlie this relationship remain unclear, but are being extensively investigated using a number of experimental models. One major hypothesis for early life physiological programming implicates fetal overexposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(180 citation statements)
references
References 172 publications
(214 reference statements)
5
170
3
2
Order By: Relevance
“…Moreover, several animal studies have demonstrated the negative consequences of embryo overexposure to glucocorticoids originating from endogenous overproduction with maternal stress or from exogenous administration. On the other hand, it is necessary to note that the influences of glucocorticoids on embryo development are balanced between positive effects that promote pregnancy versus negative effects that can compromise the pregnancy (reviewed in Drake et al 2007;Michael and Papageorghiou 2008). Only a few animal experiments have examined the effects of glucocorticoids on embryos at the preimplantation developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several animal studies have demonstrated the negative consequences of embryo overexposure to glucocorticoids originating from endogenous overproduction with maternal stress or from exogenous administration. On the other hand, it is necessary to note that the influences of glucocorticoids on embryo development are balanced between positive effects that promote pregnancy versus negative effects that can compromise the pregnancy (reviewed in Drake et al 2007;Michael and Papageorghiou 2008). Only a few animal experiments have examined the effects of glucocorticoids on embryos at the preimplantation developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, common underlying factors likely influence fetal and infant growth as well as adult physiology (5). Exposure to high levels of prenatal maternal stress (PNMS) or to exogenous GCs in utero is associated not only with poor fetal growth (6)(7)(8) but also with deregulation of the hypothalamic-pituitary-adrenal axis (9), which is involved in metabolic pathways (10) and likely represents a mediating mechanism in the developmental origins of adult diseases (2,3,11,12).…”
mentioning
confidence: 99%
“…Whereas physiological levels of GCs are required for proper metabolic control, endogenous GC deficiency or excess has been linked to a variety of metabolic diseases, including type II diabetes and obesity (Witchel and DeFranco, 2006;Drake et al, 2007;Vegiopoulos and Herzig, 2007;Zhang et al, 2015). Cortisol is the natural GC in pigs, as it is in humans.…”
Section: Introductionmentioning
confidence: 99%